Removal of SDS from biological protein digests for proteomic analysis by mass spectrometry. Issue 1 (December 2016) - Ilavenil, Soundharrajan; Al-Dhabi, Naif; Srigopalram, Srisesharam; Kim, Young; Agastian, Paul; Baaru, Rajasekhar; Choi, Ki; Arasu, Mariadhas; Park, Chun; Park, Kyung
Abstract Background Metal-organic frameworks (MOFs - MIL-101) are the most exciting, high profiled developments in nanotechnology in the last ten years, and it attracted considerable attention owing to their uniform nanoporosity, large surface area, outer-surface modification and in-pore functionality for tailoring the chemical properties of the material for anchoring specific guest moieties. MOF's have been particularly highlighted for their excellent gas storage and separation properties. Recently biomolecules-based MOF's were used as nanoencapsulators for antitumor and antiretroviral controlled drug delivery studies. However, usage of MOF material for removal of ionic detergent-SDS from biological samples has not been reported to date. Here, first time we demonstrate its novel applications in biological sample preparation for mass spectrometry analysis. Methods SDS removal using MIL-101 was assessed for proteomic analysis by mass spectrometry. We analysed removal of SDS from 0.5 % SDS solution alone, BSA mixture and HMEC cells lysate protein mixture. The removal of SDS by MIL-101 was confirmed by MALDI-TOF-MS and LC-MS techniques. Results In an initial demonstration, SDS has removed effectively from 0.5 % SDS solution by MIL-101via its binding attraction with SDS. Further, the experiment also confirmed that MIL-101 strongly removed the SDS from BSA and cell lysate mixtures. Conclusions These results suggest that SDS removal by the MIL-101 method is a practical, simple and broad applicable in proteomic sample processing for MALDI-TOF-MS and LC-MS analysis.